Tuning crystal structure of iridium-incorporated titanium dioxide nanosupport and its influence on platinum catalytic performance in direct ethanol fuel cells. (June 2021) - Huynh, T.T.; Tuan Huy, P.C.; Nguyen, H.T.Thuy; Nguyen, D.T.; Nguyen, S.T.; Pham, H.Q.
Abstract: Titanium dioxide (TiO2 ) has recently been used as a promising support for platinum (Pt)-based catalysts; however, its very low electrical conductivity and understanding the effect of the TiO2 structure on Pt electrocatalytic performance for ethanol electro-oxidation reaction (EOR) are major challenges in direct ethanol fuel cells. This study reports an easy and green approach to control the crystal structures of a robust iridium-incorporated TiO2 nanomaterial and its effect on the Pt electrocatalytic performance for EOR. A green hydrothermal route is used to fabricate iridium-modified TiO2 nanosupports with different structures by controlling the reaction temperature and time as well as solution pH without using further calcination, followed by the anchoring of Pt nanoparticles (NPs) via a surfactant-free modified reduction route. The experimental results indicate that the pure structure of the iridium-modified TiO2 nanosupport can easily be obtained by controlling the solution pH. In terms of EOR, all prepared catalysts show more effective performance than the commercial Pt/C catalyst. Among the prepared catalysts, the Pt anchored on the rutile iridium-incorporated TiO2 exhibits higher EOR performance than on the anatase iridium-incorporated TiO2 nanosupport, with negative onset potential, high current density, and electrochemical stability. The enhancement is assigned to the great adsorption and desorption ability as well as the high natural resistance to metal NPs ripening on (110) facets of the rutile structure compared with the (101) facets of the anatase structure. This exploration can offer an efficient route for tuning the structure of metal oxides and understanding the effect of the structure of the TiO2 -based support on the Pt catalytic performance. Highlights: Crystal structures of robust iridium (Ir)-modified titanium dioxide (TiO2 ) were facilely tunable via a green route. Effect of Ir-modified TiO2 structure on the Pt catalytic performance of electro-oxidation reaction (EOR) was explored. The platinum -loaded rutile Ir-modified TiO2 showed the highest EOR performance.